Implementation of multimedia interactive learning through a STEM approach based on computational thinking to improve student learning outcomes - Rambari Apandi, Anjar; Munir, Munir; Riza, Lala Septem (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This research was conducted to measure student learning outcomes using interactive multimedia with a STEM approach based on computational thinking in the informatics subject on binary numbers in class VII SMPN 1 Batujajar. The type of research used is quasi-experimental. The sample used was class VII D with a total of 32 students. The data used in this research used a pretest and posttest by giving 20 questions. Test testing is carried out by testing validity, reliability, difficulty index, and distinguishing power of questions. Data analysis uses score gain. The average pretest score before being given treatment using interactive multimedia was 50.5 and the average posttest score after being given treatment using interactive multimedia with a problem based learning model was 84.2. Thus, a gain value of 0.6814 is obtained in the medium category. It can be concluded that interactive multimedia with a STEM approach based on computational thinking can improve the learning outcomes of class VII D students at SMPN 1 Batujajar in the informatics subject on binary numbers.